Electroacupuncture relieves hyperalgesia by regulating neuronal–glial interaction and glutamate transporters of spinal dorsal horns in rats with acute incisional neck pain - Wang, Jun-ying; Zhang, Jin-ling; Chen, Shu-ping; Gao, Yong-hui; Zhang, Jian-liang; Chen, Yu; Zhang, Yue; Rong, Pei-jing; Liu, Jun-ling (Frontiers in Neuroscience, 2022)
Objective Glial cells are involved in the analgesic effect of electroacupuncture (EA) in rats with chronic neurological pain. The objective of this study was to observe the role of neuronal–glial interaction and glutamate (Glu) transporters in EA-induced acute neck pain relief in rats. Materials and methods Male rats were placed into the following five groups: control, model, EA Futu (LI18), EA Hegu (LI4)-Neiguan (PC6), and EA Zusanli (ST36)-Yanglingquan (GB34). The incisional neck pain model was established by making a longitudinal incision along the midline of the neck. The thermal pain threshold (TPT) was measured using a radiation heat detector. The immunoactivities of glial fibrillary acidic protein (GFAP), ionized calcium-binding adapter molecule 1 (Iba-1), neurokinin-1 receptor (NK-1R), Glu aspartate transporter (GLAST), and Glu transporter-1 (GLT-1) in the dorsal horns (DHs) of the cervico-spinal cord (C2–C5) were detected using immunofluorescence histochemistry. The expression levels of GFAP, Iba-1, GLAST, and GLT-1 mRNAs were determined using quantitative real-time polymerase chain reaction (PCR). Results The TPT and levels of mRNAs expression and immunoactivity of GLT-1 and GLAST were significantly decreased, and those of Iba-1 and GFAP were significantly increased in the model group than those of the control group (P < 0.05). The activated microgliacytes were gathered around the NK-1R positive neurons, and co-expression of NK-1R and astrocytes was observed in the model group. EA LI18 significantly increased the TPT and expression of GLAST and GLT-1 mRNAs (P < 0.05) and notably decreased the number of Iba-1 positive cells and Iba-l mRNA expression (P < 0.05), whereas GLAST and GLT-1 antagonists inhibited the analgesic effect of EA LI18. However, these effects, except for the downregulation of Iba-1 mRNA, were not observed in the EA ST36-GB34 group. Fewer NK-1R-positive neurons were visible in the spinal DHs in the EA LI18 group, and the co-expression of NK-1R and astrocytes was also lower than that in the three EA groups. Conclusion Electroacupuncture of LI18 had an analgesic effect in rats with neck incisions, which may be related to its functions in suppressing the neuronal–glial cell interaction through NK-1R and upregulating the expression of GLAST and GLT-1 in the spinal DHs.